Pertanian Cerdas Berbasis Internet of Things untuk Meningkatkan Produktivitas Tanaman Hidroponik - Firmansyah, Firmansyah; Wibisana, Bayu; Yusuf, Hendra Pratama; Ziad Iqbal, Muhammad; Abqari, Rifqi Sulthon (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The Al-Azhar Islamic University Technology Business Incubator (ITe UNIZAR) has the potential to increase the number and types of businesses fostered, one of which is hydroponic farming businesses. Hydroponic farming is an efficient growing method for limited land and is suitable for urban areas. However, one of the challenges faced in hydroponic cultivation is the management of AB-Mix nu-trients which are usually managed conventionally and irregularly. Utilizing the Internet of Things (IoT) can be a solution to overcome these challenges. IoT can be used to monitor plant nutrient concentrations in hydroponics in real-time. If the nutrient level is low or the air level is low, the pump will distribute the nutrients to the blending tank automatically or increase the amount of air in the available blending tank. It is hoped that the use of IoT in hydroponic systems can help MSMEs develop their business, increase productivity and increase the efficiency of cultivating plants in hydroponic media.